Answer:
3(2x + 1)(3x - 5)
Explanation:
Given
18x² - 21x - 15 ← factor out 3 from each term
= 3(6x² - 7x - 5 ) ← factor the quadratic
Consider the factors of the product of the x² term and the constant term which sum to give the coefficient of the x- term.
product = 6 × - 5 = - 30 and sum = - 7
The factors are + 3 and - 10
Use these factors to split the x- term
6x² + 3x - 10x - 5 ( factor the first/second and third/fourth terms )
3x(2x + 1) - 5(2x + 1) ← factor out (2x + 1) from each term
(2x + 1)(3x - 5)
Then
18x² - 21x - 15 = 3(2x + 1)(3x - 5)